A word portrait of Prof. N.Ch. Pattabhiramacharyulu, Retired Professor, NIT, Warangal, India - Acharyulu, K.V.L.N (Journal of Experimental Sciences, 2012)
A word portrait of Prof. N.Ch. Pattabhiramacharyulu, Retired Professor, NIT, Warangal, India